Social - Financial Effects of Universities’ Closure due to COVID-19 on Students’ Learning Resilience - M. N., Mary; Arinda, Christone (African Journal of Education,Science and Technology (AJEST), 2022)
The disruption experienced in the University education system of Uganda caused by the COVID-19 pandemic is unprecedented. The purpose of the study was to investigate the social-financial effects of Universities’ closure due to COVID-19 pandemic on students’ learning resilience. The investigation was guided by the trait resilience and social learning theories in the context of the need’s theory framework. A case study design was used and data was collected using an on-line questionnaire from 328 randomly selected students of Kyambogo University. Also, postings from student social media platforms were analysed to enrich the findings. The results indicate a decline in the students’ learning resilience from very high to moderate before and a year and half into COVID19 pandemic. Additionally, the regression results reveal that social-financial aspects explain 40% (R2 = 0.404) of the variability in student’s learning resilience. Therefore, efforts by University management, lectures, peers and family members to enhance students’ learning resilience should address the social and personal finance aspects of students in terms of having responsible social support networks and interactions on top of managing personal finance wisely. The theoretical implication is to imbue resilience and social learning theories into Maslow’s hierarchy of needs theory to generate a broad perspective of learning resilience.